Systematic Investigation of the Influence of Ethanol Blending on Sooting Combustion in DISI Engines Using High-Speed Imaging and LII - Storch, Michael; Zigan, Lars; Wensing, Michael; Will, Stefan (SAE 2014 International Powertrains, Fuels and Lubricants Meeting, FFL 2014, 2014)
Modern direct injection spark ignition (DISI) engine concepts have the drawback of higher particulate matter emission as compared to port fuel injection concepts. Especially, when driven with biofuels, the operation of DISI engines requires a deeper insight into particulate formation processes. In this study a modern optical accessible DISI engine is used. Pure isooctane, ethanol, E20 (20vol% of ethanol in isooctane) and E85 were investigated as fuels. Simultaneous OH∗-chemiluminescence and soot radiation imaging was conducted by a high-speed camera system in order to separate premixed combustion with the sooting combustion. Furthermore, a laser-induced incandescence (LII) sensor was used to measure exhaust elementary carbon mass concentration. Systematically, operation points were chosen, which correspondent to the main sooting mechanisms, poolfire, mixture inhomogeneities and global low air-fuel ratio. Furthermore, they were compared to a homogenous charge combustion strategy. Although the addition of ethanol mainly shows reduced particulate emission e.g. at homogeneous mixture conditions, for E20 at poolfire conditions the soot emission is increased compared to isooctane. In addition, E85 shows lowest soot luminosity and particle concentration for all operating points. This unexpected behavior may be explained by the dominance of chemical effects at homogenous conditions and physical fuel property effects at short mixing times. Important quantities in this context are the fuel oxygen content, the evaporation enthalpy for short mixing times, and the non-ideal vapor-liquid equilibrium of an ethanol-isooctane fuel blen